2019
DOI: 10.1016/j.toxrep.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Bombax ceiba flowers extract ameliorates hepatosteatosis induced by ethanol and relatively moderate fat diet in rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
11
0
2
Order By: Relevance
“…The high and significant serum alanine aminotransferase enzyme (ALT) level detected in the rats' group injected with 8Units can be considered as a pathological case. This case reflected hepatocytes rupture which led to the release of ALT in serum (Simon-Giavarotti et al 2002;Cotran et al 2010;Arafa et al 2019). These results are in accordance with the histological findings applied on the liver tissue as shown in Fig 2b . Also decreasing levels in serum total protein were detected in this group.…”
Section: Discussionmentioning
confidence: 99%
“…The high and significant serum alanine aminotransferase enzyme (ALT) level detected in the rats' group injected with 8Units can be considered as a pathological case. This case reflected hepatocytes rupture which led to the release of ALT in serum (Simon-Giavarotti et al 2002;Cotran et al 2010;Arafa et al 2019). These results are in accordance with the histological findings applied on the liver tissue as shown in Fig 2b . Also decreasing levels in serum total protein were detected in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Methanol was replaced with the DPPH solution as a blank control (Ab), methanol was replaced with the sample as absorbance control (Ac), and Vc and BHT were used as positive controls. The inhibition rate was calculated using the following formula (1), and the results were expressed as IC 50 value (µg/mL), which represented the sample concentration to scavenge 50% free radical.…”
Section: Diphenyl-2-picrylhydrazyl Radical Scavenging Activitymentioning
confidence: 99%
“…Equivalently, methanol was replaced with the ABTS working solution as a blank control (Ab), methanol was replaced with the sample as absorbance control (Ac), Vc and BHT were used as positive controls. The scavenging rates were calculated according to equation (1), and the results were expressed as IC 50 value (µ g/mL).…”
Section: Azino-bis-(3-ethylbenzothiazoline-6-sulfonic Acid) Radical S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bark and seeds powder has hyperlipidemic activity with a reduction in serum and tissue lipid profiles. [4] The lupeol from stem bark exhibits the inhibitory effect on human umbilical venous endothelial cells (HUVECs) tube formation without affecting the growth of tumor cell lines. [5] It is reported that there are triterpenoid compounds in the stem bark extract, which could be responsible for lowering blood glucose levels.…”
mentioning
confidence: 99%